2017
DOI: 10.6000/1927-5129.2017.13.54
|View full text |Cite
|
Sign up to set email alerts
|

Response of Conjunctive Use of Fresh and Saline Water on Growth and Biomass of Cotton Genotypes

Abstract: A pot experiment was conducted to study the effects of conjunctive use of saline and fresh water on the growth and biomass of cotton crop and to observe varietal variability for salinity tolerance and ion contents of cotton genotypes. Four cotton genotypes (Sindh-1, BT-121, CRISS-494, CRISS-588) were irrigated with four treatments, C1 (control+ tape water), C2 (EC 4.0 dS m-1, throughout growth period), ( (six irrigation with C2 + six irrigation with C1), C3 (EC 8.0 dS m-1, throughout growth period), (six irrig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…With wheat, Mojid and Hossain [14] and Mojid et al [12] stated that saline water irrigation could be applied at later growth stages when plants have better salinity tolerance. On the other hand, the cotton yield contributing attributes and yield was significantly higher when fresh water was used to irrigate and significantly decreased with increasing the levels of salinity from 4-12 dS m −1 [44]. In this study, irrigation levels also significantly (p < 0.001) depressed the yield components of sunflower-like seed weight head −1 , as well as sunflower seed yield, if a single application of LSW was followed by two applications with MSW (Tables 3 and 4).…”
Section: Variation Of Sunflower Seed Yield and Yield Componentsmentioning
confidence: 98%
“…With wheat, Mojid and Hossain [14] and Mojid et al [12] stated that saline water irrigation could be applied at later growth stages when plants have better salinity tolerance. On the other hand, the cotton yield contributing attributes and yield was significantly higher when fresh water was used to irrigate and significantly decreased with increasing the levels of salinity from 4-12 dS m −1 [44]. In this study, irrigation levels also significantly (p < 0.001) depressed the yield components of sunflower-like seed weight head −1 , as well as sunflower seed yield, if a single application of LSW was followed by two applications with MSW (Tables 3 and 4).…”
Section: Variation Of Sunflower Seed Yield and Yield Componentsmentioning
confidence: 98%
“…Li et al (2019) opined that under fresh water shortage conditions, application of non-saline water at the seedling and flowering stage while saline-water application at fruit set-stage was the most suitable mode of irrigation for high yield production of tomato without deteriorating the soil properties. Gandahi et al (2017) concluded from a pot experiment that cotton gave the economical yield if six irrigations were provided with saline water and six irrigations with non-saline water in a conjunctive manner. Similarly, Chen et al (2018) suggested that the optimal mixing of nonsaline and saline water may be more beneficial for cotton production and avoid secondary salinization when using saline water.…”
Section: Research Articlementioning
confidence: 99%
“…In a pot experiment, Gandahi et al (2017) studied the response of different cotton varieties against conjunctive use of non-saline and saline water. They concluded that cotton genotypes performed better when six irrigations were provided with fresh water and six irrigations with salty water in a conjunctive manner.…”
Section: Introductionmentioning
confidence: 99%